Business, biodiversity and ecosystem services: Evidence from large-scale survey data - Marcus Wagner (Business Strategy and the Environment, 2022)
This paper analyses data from a large-scale survey on corporate action to support biodiversity and ecosystem services undertaken by firms of all sizes and across manufacturing industries. The analysis focuses on Germany as the largest economy by GDP in the European Union and analyses the uptake of activities directly aimed at protecting biodiversity and ecosystem services compared to the uptake of other environmental protection activities. It furthermore investigates how activity and tool adoption as well as risk assessments vary with firm size and across industries, and with implementing environmental management systems. The analysis finds tensions between risk perception and activities pursued for biodiversity protection, largely because firms shy away from substantive action. It reveals that smaller and medium-sized firms are less active and that environmental management systems are not conducive to corporate activities in support of biodiversity and ecosystem services.
Keywords: 650; biodiversity; ecosystem services; SME; survey; symbolic action; tensions